Effects of various operating conditions on the performance of a CO2 air conditioning system for trains. (November 2019) - Jiang, Fuzheng; Wang, Yufeng; Yu, Binbin; Wang, Dandong; Shi, Junye; Chen, Jiangping
Highlights: Performance of a two circuits CO2 train AC system has been experimentally tested under different operating conditions. An introduction of a numerical model of CO2 train AC system has been presented. Effects of operating conditions on the train AC system have been discussed in detail. An error analysis between the test and the numerical has been presented. A related equation between the gas cooler outlet temperature and the optimum high pressure is presented. Abstract: This paper aims to investigate the effects of different operating parameters on the performance of a transcritical CO2 air conditioning system for trains. Similar designs of automotive CO2 air conditioning system are used in the train system such as internal heat exchanger (IHX) to improve the system efficiency. Experimental results are presented for the performance characteristics of the CO2 train air conditioning system with two independent circuits under different test conditions such as different refrigerant charge amount, compressor working frequency, indoor air volume flow rate and outdoor chamber temperature. Two different operating modes of the two circuits are also included in this research. For mode I while only one circuit is working, the test results show that the maximum cooling capacity and coefficient of performance (COP) is 24.3 kW and 2.7, during 55 Hz and 40 Hz compressor working frequency conditions respectively. Also, the cooling capacity and COP reach the minimum, 16.2 kW and 1.5, when the outdoor chamber temperature is 45  °C. For mode II while both two circuits are working, the results show that the cooling capacity and COP are 42.0 kW and 2.4, respectively. The system performance error between the test and numerical modeling which directs the design of the system is within ±5%. Furthermore, an optimum high pressure control algorithm for the transcritical CO2 cycle of the train AC system is also presented.